Macrophage activation syndrome in a newborn: report of a case associated with neonatal lupus erythematosus and a summary of the literature - Veerle Heijstek; Meelad Habib; Roel van der Palen; Remco van Doorn; Petra Hissink Muller (BMC, 2021)
Abstract Background Macrophage activation syndrome (MAS) is a life-threatening hyperinflammatory syndrome and is caused by a severely dysregulated immune response. It has rarely been associated with neonatal lupus. Case presentation We present a female neonate with MAS born to a mother who had cutaneous lupus erythematosus with circulating anti-nuclear antibodies (ANA), anti-SSA, anti-SSB and anti-extractable nuclear antigen (anti-ENA) antibodies. Because of neonatal lupus (NLE) with a total atrioventricular block, epicardial pacemaker implantation was required on the sixth day of life. Following surgery she developed non-remitting fever and disseminated erythematous skin lesions. A diagnosis of MAS was made based on these symptoms, with hyperferritinemia, elevated transaminases, hypertriglyceridemia, and a skin biopsy that showed hemophagocytosis. Our patient was treated with steroids for 3 months with good effect. No relapse has occurred. Conclusions MAS is a rare complication of neonatal lupus that may be difficult to diagnose, but needs to be treated promptly. In this article, pathogenesis and overlap of MAS and hemophagocytic lymphohistiocytosis (HLH) has been described. Diagnosis of MAS can be difficult. Different diagnostic criteria are used in both diagnosing MAS and HLH. Validated criteria for diagnosis of MAS in other disease than systemic onset JIA have not been validated yet. In NLE, diagnosing MAS is even more difficult, since skin lesions are already common in NLE. We show the potential additional value of skin biopsy in diagnosing MAS.